1999
DOI: 10.1083/jcb.144.5.883
|View full text |Cite
|
Sign up to set email alerts
|

The Release of Cytochrome c from Mitochondria during Apoptosis of NGF-deprived Sympathetic Neurons Is a Reversible Event

Abstract: During apoptosis induced by various stimuli, cytochrome c is released from mitochondria into the cytosol where it participates in caspase activation. This process has been proposed to be an irreversible consequence of mitochondrial permeability transition pore opening, which leads to mitochondrial swelling and rupture of the outer mitochondrial membrane. Here we present data demonstrating that NGF-deprived sympathetic neurons protected from apoptosis by caspase inhibitors possess mitochondria which, though dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
201
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(221 citation statements)
references
References 50 publications
(68 reference statements)
18
201
1
1
Order By: Relevance
“…Despite all the data implicating the PT-pore in cell death, a number of caveats have been raised against the PT-pore: Some investigators failed to see a dependence on the PT-pore for Bax-and Bid-induced apoptosis [16][17][18][19]. Also, in some apoptosis scenarios Bax-induced release of cytochrome c could not be inhibited by bongkrekic acid and or CsA [20].…”
Section: Evidence Against the Pt-pore In Cell Death And Modificationsmentioning
confidence: 99%
“…Despite all the data implicating the PT-pore in cell death, a number of caveats have been raised against the PT-pore: Some investigators failed to see a dependence on the PT-pore for Bax-and Bid-induced apoptosis [16][17][18][19]. Also, in some apoptosis scenarios Bax-induced release of cytochrome c could not be inhibited by bongkrekic acid and or CsA [20].…”
Section: Evidence Against the Pt-pore In Cell Death And Modificationsmentioning
confidence: 99%
“…In many cell types mitochondrial membrane permeabilization (MMP) is considered as the point of nonreturn in the cell suicide (Ferri and Kroemer, 2001). However, in sympathetic neurons for example, this event appears to be reversible and death can be circumvented downstream of cytochromic c release (Martinou et al, 1999;Deshmukh et al, 2000;Tolkovsky et al, 2002). Whether it is also the case in cancer cells remains to be determined.…”
Section: Mitochondrial Membrane Permeabilizationmentioning
confidence: 99%
“…Because OPA1 appears to be required for the integrity of mitochondrial cristae and also for normal mitochondrial morphology, this raises the possibility that apoptosis-associated release of OPA1 into the cytosol underpins the extensive fragmentation of the mitochondrial network that is frequently observed during this mode of cell death. [15][16][17] Whereas the latter proposal remains speculative, it does seem that OPA1 serves an indispensable role in organizing mitochondrial cristae into their correct form and that interference with the function of this protein results in an increased potential for cytochrome c escape.…”
Section: Opa1 Regulates Mitochondrial Cristae Integritymentioning
confidence: 99%
“…2 Although it is clear that extensive mitochondrial fission is associated with apoptosis, [15][16][17] it remains a matter of debate as to whether this phenomenon also contributes to cytochrome c efflux. Although initial studies from Youle's laboratory suggested that interfering with the process of mitochondrial fission could delay the release of cytochrome c and consequent apoptosis, 20 subsequent reports suggest that these events may be coincident rather than functionally interconnected.…”
Section: Mitochondrial Fission and Apoptosismentioning
confidence: 99%